Some cool considerations of external lumbar drainage during its widespread application in neurosurgical practice: a long way to go. Issue 1 (December 2016) - Li, Guichen; Zhang, Yang; Zhao, Jinchuan; Han, Zhiguo; Zhu, Xiaobo; Hou, Kun
Abstract External lumbar drainage (ELD) has gained wide popularity in neurosurgical practice since its' first introduction by F. Vourc'h in 1963. It manifests encouraging prospects in control of refractory intracranial hypertension, prevention of complications secondary to aneurysmal subarachnoid hemorrhage, prediction of shunt respondency in normal pressure hydrocephalus, management of cerebrospinal fluid (CSF) leakage, and application in bacterial meningitis and ventriculitis. But many questions on the efficacy and safety of ELD are remained to be answered by future studies. CSF overdrainage and ELD-related meningitis are the two most common and fatal complications due to inappropriate usage of ELD. Randomized controlled trials are badly in need to more safely and rationally guide the clinical application of ELD.